A compreensão do paciente sobre o termo de consentimento informado em cirurgia plástica - Neder Netto, Jose [UNIFESP] (2019)
Introduction: With the increase in the numbers of complaints and lawsuits against physicians however dealing with possible medical error causing the large increase in the judicialization of medicine in recent years and great socio-economic impact. Studies in Brazil are lacking to understand this phenomenon and its meanings. Objective: To describe and compare the patient's understanding of informed consent before and after plastic surgery. Method: Prospective analytical descriptive study, through the application of a questionnaire on the informed consent before and after the accomplishment of plastic surgery. To relate the patients schooling to the questionnaire answers before and after the surgery. Result: Question 15 was the only one in which we noticed a change in comprehension between before and after surgery (p = 0,016), where the questionnaire response before surgery was better than the questionnaire applied after the operation. According to estimates of Spearman's correlation coefficient (s) we noticed that the higher is the scholarity the higher is the comprehension only in question 4 (s = 0,151; p = 0,045) of before surgery and in question 1 (s = 0,180; p = 0,046) after surgery, in the other questions there was not a difference in comprehension regarding schooling. Conclusion: The patient's comprehension is great about the information of the surgeries, its results, possible complications and postoperative evolutions.